Principles and Applications of Seismic Monitoring Based on Submarine Optical Cable - Junzhe Yu; Pengbai Xu; Zhangjun Yu; Kunhua Wen; Jun Yang; Yuncai Wang; Yuwen Qin (Sensors, 2023)
Submarine optical cables, utilized as fiber-optic sensors for seismic monitoring, are gaining increasing interest because of their advantages of extending the detection coverage, improving the detection quality, and enhancing long-term stability. The fiber-optic seismic monitoring sensors are mainly composed of the optical interferometer, fiber Bragg grating, optical polarimeter, and distributed acoustic sensing, respectively. This paper reviews the principles of the four optical seismic sensors, as well as their applications of submarine seismology over submarine optical cables. The advantages and disadvantages are discussed, and the current technical requirements are concluded, respectively. This review can provide a reference for studying submarine cable-based seismic monitoring.